2012
DOI: 10.1016/j.bone.2012.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Cortical microstructure and estimated bone strength in young amenorrheic athletes, eumenorrheic athletes and non-athletes

Abstract: CONTEXT Lower bone density in young amenorrheic athletes (AA) compared to eumenorrheic athletes (EA) and non-athletes may increase fracture risk during a critical time of bone accrual. Finite element analysis (FEA) is a unique tool to estimate bone strength in vivo, and the contribution of cortical microstructure to bone strength in young athletes is not well understood. OBJECTIVE We hypothesized that FEA-estimated stiffness and failure load are impaired in AA at the distal radius and tibia compared to EA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
102
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 50 publications
8
102
1
2
Order By: Relevance
“…These data sug- (3). Of interest, menarchal age was not a significant predictor of any HSA measure in our study, in contrast to studies of microarchitecture of the distal tibia and distal radius in athletes, which found that increasing menarchal age was associated with greater impairment of bone density and structure (2,3). Girls involved in Ն16 hours/wk of moderate to vigorous activity were noted to have a higher risk of stress fractures in one study, suggesting that greater volume or intensity of exercise is deleterious to bone health, despite the effects of mechanical loading (19).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…These data sug- (3). Of interest, menarchal age was not a significant predictor of any HSA measure in our study, in contrast to studies of microarchitecture of the distal tibia and distal radius in athletes, which found that increasing menarchal age was associated with greater impairment of bone density and structure (2,3). Girls involved in Ն16 hours/wk of moderate to vigorous activity were noted to have a higher risk of stress fractures in one study, suggesting that greater volume or intensity of exercise is deleterious to bone health, despite the effects of mechanical loading (19).…”
Section: Discussioncontrasting
confidence: 60%
“…In studies using HRpQCT, we have reported that eumenorrheic endurance athletes have higher estimates of bone strength, namely stiffness and failure load, at the distal tibia than nonathletes, whereas amenorrheic athletes do not differ from nonathletes (3). These data and reports of a higher prevalence of fractures in amenorrheic compared with eumenorrheic athletes (20,21) suggest that benefits of mechanical loading on bone through exercise may be attenuated in the amenorrheic (hypogonadal) state.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Historically, the majority of studies focusing on the effects of menstrual cycle disturbances have naturally focused on BMD, the bone health variable clinically used to diagnose osteoporosis. However, with technological advances in bone health imaging, such as HSA, and greater accessibility to other modes of bone imaging, such as QCT, there has been an additional focus on bone geometry among female athletes with menstrual disturbances [5][6][7]12,27,50]. These advancements in the field of women's bone health are important due to the major influence that bone geometry has on overall bone health.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle mass and size are consistent and positive predictors of cortical bone geometry, predominantly because of their role in promoting bone mineral deposition toward the periosteum [14,[30][31][32][33] …”
Section: Muscle and Cortical Bone Geometry Volumetric Density And Stmentioning
confidence: 99%